Worst-month rain statistics for radiowave propagation study in Malaysia - Chebil , J. (IEEE, 1999)
A study of the worst-month rainfall rate statistics for the Malaysian environment is presented. Rain rate data with 1 min integration time were collected in the Universiti Teknologi Malaysia and the Universiti Sains Malaysia. The relationship between the worst month and the yearly probabilities is presented and the ITU-R model verified. For better precision, new values are proposed for the parameters Q1 and ÃŸ in Malaysia.